New airborne retrieval approach for trade wind cumulus properties under overlying cirrus. Issue 9 (7th May 2013) - Werner, F.; Siebert, H.; Pilewskie, P.; Schmeissner, T.; Shaw, R. A.; Wendisch, M.
Abstract : [1] A new retrieval method is presented to derive the optical thickness τ and effective droplet radius r eff of shallow cumulus in the presence of overlying thin cirrus. This new approach allows for a retrieval without a priori knowledge of the microphysical and optical properties of the overlying cirrus. The retrieval is applied to helicopter‐borne solar spectral reflectivity measurements gathered by the Spectral Modular Airborne Radiation measurements sysTem (SMART‐HELIOS) above trade wind cumuli near Barbados. Collocated microphysical cumulus properties (liquid water content, effective droplet radius, droplet number concentration) were measured by in situ instruments installed on the Airborne Cloud Turbulence Observation System (ACTOS). Cloud inhomogeneities lead to an underestimation of retrieved τ of up to 114 %, while r eff is biased by up to 27 % . Moreover, misrepresentation of the overlying cirrus may cause an overestimation of the classically retrieved cumulus r eff of up to 50 % and an underestimation of τ of up to 6 % . The new retrieval, effectively correcting for the influence of overlying cirrus, enables reliable estimates of τ of the cumuli for optically thin, overcast cirrus conditions and reduces the retrieval error for r eff of the cumuli by almost 50 % . Agreement between in situ measured and retrieved r eff is in the range of ±1 μ m. The retrieval can also reproduce the wide range of in situ measured mean r eff (7–18  μ m), which is a result of different aerosol load and cloud top heights on the different flight days. The observed τ ranges between 5 and 36. Key Points: Cloud inhomogeneity and overlying cirrus affects retrieval New retrieval approach mitigates effect of overlying cirrus New Retrieval and in situ results compare within measurement uncertainty